Enhancing Student’s Sustainability Awareness through PBL-ESD on Microplastic Pollution - Syifa Ayugea (Universitas Negeri Surabaya, 2026)
This research aims to develop and implement a didactic design based on Problem-Based Learning integrated with Education for Sustainable Development (PBL-ESD) to enhance sustainability awareness and science literacy of students on the topic of microplastic pollution. This research uses a Didactical Design Research (DDR) approach with high school students in Sukabumi Regency as subjects. Findings show that the didactic design of PBL-ESD, developed in accordance with the steps of PBL and focused on sustainability issues, can support active participation of learners in solving actual problems related to microplastic pollution. In addition, the learning design and the tested assessment tools demonstrate support for improving scientific literacy while also increasing students' sustainability awareness. This implementation proves that the integration of PBL and ESD provides a relevant learning experience and prepares students with critical thinking and problem-solving skills related to environmental issues.